1979
DOI: 10.1073/pnas.76.11.5704
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of tumor cells with vascular endothelial cell monolayers: a model for metastatic invasion.

Abstract: The interactions of tumorigenic and nontumorigenic human and rodent cells with vascular endothelial cells and their underlying extracellular matrix were studied in culture. Gospodarowicz (9)(10)(11). Endothelial cells were used at passage 4-8. BAE cells were routinely cultured in Dulbecco's modified Eagle's medium supplemented with 10% calf bovine serum (Irvine Scientific), and human umbilical cord endothelial cells were cultured in medium 199 plus 20% fetal bovine serum. Fibroblast growth factor was purified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
115
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(123 citation statements)
references
References 30 publications
8
115
0
Order By: Relevance
“…The prostate epithelial cell then generates a pseudopodial extension, which penetrates the endothelial cell layer, the endothelial cells retract and the prostate cell moves through the endothelial barrier. As with the migration across endothelia observed in melanoma cells, prostate epithelial trans-migration is considerably slower than leukocyte transmigration, with 29% of cells completing the transit within 4 h. This extravasation time is comparable to that observed for melanoma cells (Voura et al, 1998), rat ascites hepatoma cells (Ohigashi et al, 1989) and other tumour cells (Kramer and Nicolson, 1979). However, it has been shown that over 50% of monocytes can cross an endothelium within the first hour of contact (Sandig et al, 1997) without inducing endothelial cell retraction.…”
Section: Discussionsupporting
confidence: 63%
“…The prostate epithelial cell then generates a pseudopodial extension, which penetrates the endothelial cell layer, the endothelial cells retract and the prostate cell moves through the endothelial barrier. As with the migration across endothelia observed in melanoma cells, prostate epithelial trans-migration is considerably slower than leukocyte transmigration, with 29% of cells completing the transit within 4 h. This extravasation time is comparable to that observed for melanoma cells (Voura et al, 1998), rat ascites hepatoma cells (Ohigashi et al, 1989) and other tumour cells (Kramer and Nicolson, 1979). However, it has been shown that over 50% of monocytes can cross an endothelium within the first hour of contact (Sandig et al, 1997) without inducing endothelial cell retraction.…”
Section: Discussionsupporting
confidence: 63%
“…Most works on the transendothelial migration of cancer cells show the formation of gaps in the EC monolayer that allow direct access of TCs to the exposed subendothelial matrix. 21,22,[37][38][39] In this regard, it has been reported that TC-EC interactions induce a rapid EC-EC dissociation, which correlates with a dramatic loss of VE-cadherin staining around the TCs. 34 In contrast, only local changes in VE-cadherin staining at sites of TC-EC contact were reported using a 3-dimensional EC culture system on matrigel, 40 in accordance with our results with collagen gels.…”
Section: Discussionmentioning
confidence: 99%
“…The various components of tumor cell-endothelial cell interaction can be replicated in vitro by challenging a monolayer of human umbilical vein endothelial cells (HUVEC) with cancer cells. Studies performed with electron and phasecontrast microscopy suggest that the in vitro sequence of events fairly represent the in vivo metastatic process 6 . Here, we describe an electricalimpedance based technique that monitors and quantifies in real-time the invasion of endothelial cells by malignant tumor cells.…”
Section: Introductionmentioning
confidence: 99%